The use of germicidal ultraviolet light, vaporised hydrogen peroxide and dry heat to decontaminate face masks and filtering respirators contaminated with an infectious norovirus. Issue 1 (March 2021) - Wielick, Constance; Ludwig-Begall, Louisa F.; Dams, Lorène; Razafimahefa, Ravo M.; Demeuldre, Pierre-Francois; Napp, Aurore; Laperre, Jan; Jolois, Olivier; Farnir, Frédéric; Haubruge, Eric; Thiry, Etienne
Summary: In the context of the SARS-CoV-2 pandemic, reuse of surgical masks and filtering facepiece respirators has been recommended. Their reuse necessitates procedures to inactivate contaminating human respiratory and oral pathogens. We previously demonstrated decontamination of masks and respirators contaminated with an infectious SARS-CoV-2 surrogate via ultraviolet germicidal irradiation, vaporised hydrogen peroxide, and use of dry heat. Here, we show that these same methods efficiently inactivate a more resistant, non-enveloped oral virus; decontamination of infectious murine norovirus-contaminated masks and respirators reduced viral titres by over four orders of magnitude on mask or respirator coupons.